Palang Pintu Kereta Api Otomatis Berbasis Arduino - Pratama, Shendy; Taqwa, Ahmad; Salamah, Irma (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2019)
This automatic train doorstop is made by using two infrared sensors and the sensor's piezeotronic sensor will be controlled by Arduino, this sensor will be useful if it detects the arrival of a train, if the train has passed this sensor then automatically the doorstop will be closed, when the train passes one more sensor then the doorstop will open automatically. For information to the community that there will be a train passing, it must be equipped with a bazzer and other indicator lights. With this automatic doorstop, the level of accident at the railroad crossing will decrease.